CONFLICT OF INTEREST PROBLEM IN THE MANAGEMENT-CONTROLLED FIRMS - Dewi Ratnaningsih; Jogiyanto Hartono (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
This study hypothesizes that the conflict of interest problem exists in themanagement-controlled firms. The problem does not exist in the owner-controlled firms.This study supports these hypotheses.The conflict of interest problem occurs in the management-controlled firmsbecause managers tend to emphasize their wealth by increasing sales or profit but stockreturns at the expense of shareholders’ wealth. Shareholders are more concerned withthe increase of stock returns, which is related directly to their wealth. On the otherhand, in the owner-controlled firms, since the managers are also the owners of thefirms, the conflict of interest problem does not exist.The conflict of interest problem still persists even though CEOs have beencompensated well. The problem cannot be solved by how much CEOs are paid, but byhow they are paid. The problem can be reduced by designing compensation scheme thatincreases the ownership of the CEOs. This situation had already been recognized by theU.S. firms, that of the 374 firms in the sample, 80% or 300 firms are the ownercontrolledfirms.Keywords: Compensation, conflict of interest, agency relationship.